FINANCING OF THE INNOVATIVE PROJECTS IN THE AGRO-INDUSTRIAL COMPLEX OF KAZAKHSTAN - B. Zhumanova (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка, 2013)
In the article are considered theoretical and practical issues of financial support of innovative development of agriculture in Kazakhstan. Defined system-wide problems that impede the full development of innovative agro-industrial complex of Kazakhstan. It is established that a promising start innovative development of agriculture of Kazakhstan are the reproduction of agricultural innovation and development in the mass practice of improved methods of agricultural production.